1927 Ind. Acts 53-54 - (:unkn) unknown (My University, 1927)
Crimes-Burglary with Explosives, Electricity or Gas-Punishment, ch. 19, § 1: Prohibited breaking into and entering, with intent to commit a felony, and attempts to open or attempt to open any vault, safe, or other secure place by the use of nitroglycerin, dynamite, gunpowder, or any other explosive, or by the use of electricity to burn or melt, or use oxycetyline gas, or any other gas to open such containers, shall be deemed guilty of burglary with explosives, electricity, or gas. Violators shall be imprisoned not less than ten years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME